Advanced Characterization Techniques for Interface in All‐Solid‐State Batteries. Issue 9 (1st July 2020) - Li, Yuyu; Gao, Zhonghui; Hu, Fei; Lin, Xing; Wei, Ying; Peng, Jian; Yang, Jiayi; Li, Zhen; Huang, Yunhui; Ding, Han
Abstract: The interface is a critical factor of electrochemical performance for all‐solid‐state batteries (ASSBs). Comprehending the composition, structure, morphology, and their evolution in the interface during charge/discharge cycling is greatly important for the development and practical application of ASSBs. The characterization techniques are very crucial and powerful for investigating the interface properties of ASSBs. This review briefly describes how the interface is generated in ASSBs, and then emphatically summarizes some important advanced techniques used to characterize the interface in ASSBs. The principle, advantage, and application of the techniques in the interface investigation are systematically discussed. This review provides fundamental insights and perspectives for developing the characterization techniques to deeply understand the interfacial behaviors of ASSBs, which is valuable for accelerating the commercialization of ASSBs used in electronic devices, electric vehicles, and large‐scale energy storage. Abstract : The interface is a critical factor of electrochemical performances for all‐solid‐state batteries (ASSBs). This review not only describes how the interface is generated in ASSBs, but emphatically summarizes some important advanced techniques used to characterize the interface in ASSBs, including principle, advantage and application, which is valuable for deeply understanding the interfacial behaviors of ASSBs.